Teologia e ecologia: contribuições de Tomás de Aquino e do Papa Francisco em busca de superar a crise ecológica vigente - Delfino, Claudio Antonio (2025)
The relationship between God, the world, and man has existed since ancient Greek times, even with the differences of each era. The Judeo-Christian faith teaches us that God, out of love and not necessity, created everything. However, in the last two centuries, it seems that man, dispensing with God and considering himself the absolute master of history, has begun to relate to the world as a mere object, accelerating the current ecological crisis. Therefore, the general objective of this reflection is to verify whether the thought of Thomas Aquinas and Pope Francis can contribute to the construction of plausible, alternative, and constructive paths to address the current ecological crisis that afflicts our Common Home. This objective will be subdivided into three specific moments, resulting in the three chapters of this investigation. These are: To outline the “principles” (or perspectives) necessary to obtain a better, albeit approximate, diagnosis of the current reality, seeking to highlight its main effects and causes that shape this serious global ecological crisis, particularly based on the legacy of Pope Francis’ thought; To present the main elements of Thomas Aquinas’ thought that may contribute to the beginning of a process, even if long-term, but that starts today, from each individual and the institutions responsible for the well-being of Creation; To create an interface between the thought of Pope Francis and Thomas Aquinas, seeking to extract common elements from them that can contribute to the building of alternative and hopeful paths in the sad scenario that plagues our Common Home. It is believed that, given the evident existence of such a crisis affecting the entire Earth, with theological work open to human reason and its various branches of knowledge, the purpose of shedding light on the reality in which we find ourselves justifies this initiative. Additionally, it raises the questions: Is there a relationship between the Trinity and the created world? Is it possible to find God’s fingerprints in Creation? What is human responsibility in the face of the ecological crisis? Is there still hope for reordering the current ecological disorder? What are the paths to achieve this goal? As a result of this investigative effort, it can be stated: There is a participation of creatures in the Trinitarian mystery, and everything is intimately interconnected; The world is not a mere object at human disposal but a gift from God that has been entrusted to man from the beginning to be guarded and cultivated; Human beings are not God but must humbly acknowledge their dependence on Him; The centrality of the mystery of the Incarnation of Jesus Christ for the redemption of all must be recognized; An urgent ecological conversion of humanity is necessary, with a view to caring for the earth and the most vulnerable; Hope should not be limited to the present moment but should be open to eternity, where we will pass from the garden of the world to the house of the Father, for from Him we came and to Him we shall return. The research methodology is to see, judge, and act